A Lei de Responsabilidade Fiscal e a construção da política econômica nacional da União - Nascimento, Esdras Belleza do (2018)
This paper presents an analysis of the Fiscal Responsability Act as an enforcement tool of the national economic policy of the Union. Besides being an important management tool for the Public Administrator, the LRF introduced effective changes in the history of public management in Brazil. The LRF is a code of conduct for all public administrators and an efficient tool for managers to better control the resources that are available to them, which affects the three branches of government (Executive, Legislative and Judiciary), and the three spheres of government (federal, state and municipal). It first discusses the historical context of the development of the LRF. Next, it analyzes the constitutional grounds of the LRF and its structural principles. Lastly, it explores the current challenges of the LRF.